Reducing Uncertainty in 21st Century Sea-Level Predictions and Beyond - Siegert, Martin; Pearson, Pam (Frontiers in Environmental Science, 2021)
Sea-level rise is one of the most critical issues the world faces under global warming. Around 680 million people (10% of the world’s population) live in low-lying coastal regions that are susceptible to flooding through storm surges and from sea-water infiltration of fresh groundwater reserves, degradation of farmland and accelerated coastal erosion, among other impacts. Rising sea level will exacerbate these problems and lead to societal impacts ranging from crop and water-supply failures to breakdowns of city infrastructures. In time, it is likely such changes will necessitate the migration of people with substantial economic cost and social upheaval. Here, we discuss the physical processes influencing 21st Century sea-level rise, the importance of not using 2100 alone as a benchmark, the changes that are already locked in, especially after 2100, and those that can be avoided. We also consider the need for both adaptation and mitigation measures and early warning systems in this challenging global problem. Finally, we discuss how the scientific prediction of sea level rise can improved through international coordination, cooperation and cost sharing.